Sosialisasi Tindakan Pencegahan Kondisi Kritis Dari Diabetes Mellitus Tipe II - Riani, Riani; Muzakir, Muzakir; Nislawati, Nislawati; Tania, Bella (Dedikasi: Jurnal Pengabdian Pendidikan dan Teknologi Masyarakat, 2024)
Patients with impaired glucose tolerance due to excessive insulin secretion and glucose levels will be maintained at normal levels or slightly increased. However, the role of B cells if they are unable to keep up with the increased need for insulin, then glucose levels will increase and type II DM will occur. Despite the impaired insulin secretion that is characteristic of type II DM, there is still insulin in adequate amounts to prevent the breakdown of fat and the production of ketone bodies that accompany it, therefore diabetic ketoacidosis does not occur in type II DM, however, type II DM does. Uncontrolled will cause other acute problems such as non-ketotic hypoglycemic hyperglycemic syndrome (HHNK). The problems that arise here are Mrs. Y's partners/family do not know 1) the conditions that pose a risk of a critical condition in people with diabetes mellitus, her family/Mrs. Y do not know what can prevent DM people from being in a critical condition. 2) Mrs. Y stated that his blood sugar tends to rise because he is not disciplined in consuming and managing food intake. The results of the conversation between the Tuanku Tambusai Hero University service team and one of the residents of the Bangkinang Seberang Village, Muara Uwai Village, namely Mrs. Y, who also has diabetes mellitus from heredity and unhealthy eating habits, which results in an increase in blood sugar. Mrs. Y was diagnosed with DM in May 2022, when her blood sugar level was detected at 350 mg/dL. She was advised by her doctor to undergo insulin therapy for life. If you experience critical signs and symptoms of DM, immediately go to the health service so that you can get action quickly and precisely.